Poverty in the Early Church and Today A Conversation - Walton, Steve (Bloomsbury Academic, 2018)
This innovative volume focuses on the significance of early Christianity for modern means of addressing poverty. The volume offers rigorous study of poverty and its alleviation in both earliest Christianity and today's world. In this light, in seven major areas, an expert in early Christianity in its Jewish and Greco-Roman settings is paired with an expert in modern strategies for addressing poverty and benefaction. They each address the same topic from their respective areas of expertise, and respond to each other's essays. The chapters present the complex ways in which early Christian ideas and practices relate to modern ideas and practices and vice versa. The book addresses both continuities and discontinuities between the ancient world and today. As such the volume seeks to inform and engage church leaders, those working in NGOs concerned with poverty, and all interested in these crucial issues, both Christian and not.